Local control of superconductivity in a NbSe2/CrSBr van der Waals heterostructure - Junhyeon Jo; Yuan Peisen; Haozhe Yang; Samuel Mañas-Valero; José J. Baldoví; Yao Lu; Eugenio Coronado; Fèlix Casanova; F. Sebastian Bergeret; Marco Gobbi; Luis E. Hueso (Nature Communications, 2023)
Abstract Two-dimensional magnets and superconductors are emerging as tunable building-blocks for quantum computing and superconducting spintronic devices, and have been used to fabricate all two-dimensional versions of traditional devices, such as Josephson junctions. However, novel devices enabled by unique features of two-dimensional materials have not yet been demonstrated. Here, we present NbSe2/CrSBr van der Waals superconducting spin valves that exhibit infinite magnetoresistance and nonreciprocal charge transport. These responses arise from a unique metamagnetic transition in CrSBr, which controls the presence of localized stray fields suitably oriented to suppress the NbSe2 superconductivity in nanoscale regions and to break time reversal symmetry. Moreover, by integrating different CrSBr crystals in a lateral heterostructure, we demonstrate a superconductive spin valve characterized by multiple stable resistance states. Our results show how the unique physical properties of layered materials enable the realization of high-performance quantum devices based on novel working principles.